Analysis of Amino Acid Mutations of the Foot-and-Mouth Disease Virus Serotype O Using both Heparan Sulfate and JMJD6 Receptors - Gyeongmin Lee; Ji-Hyeon Hwang; Aro Kim; Jong-Hyeon Park; Min Ja Lee; Byounghan Kim; Su-Mi Kim (Viruses, 2020)
Foot-and-mouth disease (FMD) is an economically devastating animal disease. Adapting the field virus to cells is critical to the vaccine production of FMD viruses (FMDV), and heparan sulfate (HS) and Jumonji C-domain-containing protein 6 (JMJD6) are alternative receptors of cell-adapted FMDV. We performed serial passages of FMDV O/SKR/Andong/2010, classified as the O/Mya-98 topotype/lineage and known as a highly virulent strain, to develop a vaccine seed virus. We traced changes in the amino acid sequences of the P1 region, plaque phenotypes, and the receptor usage of the viruses, and then structurally analyzed the mutations. VP3 H56R and D60G mutations were observed in viruses using the HS receptor and led to changes in the hydrogen bonding between VP3 56 and 60. A VP1 P208L mutation was observed in the virus using the JMJD6 receptor during cell adaptation, enabling the interaction with JMJD6 through the formation of a new hydrogen bond with JMJD6 residue 300. Furthermore, VP1 208 was near the VP1 95/96 amino acids, previously reported as critical mutations for JMJD6 receptor interactions. Thus, the mutation at VP1 208 could be critical for cell adaptation related to the JMJD6 receptor and may serve as a basis for mechanism studies on FMDV cell adaptation.